Diffusion of Innovation Process of the ESQ Public Speaking Model in the Communication Training Development - Yusran Efendi; Shinta Kristanti; Qilan Umara Ridwan; Yolanda Stellarosa (Ikatan Sarjana Komunikasi Indonesia, 2024)
Public speaking is an important communication ability that influences numerous areas of life, including business, school, and daily life. As the generation's decision-making and education evolve, public speaking modules should be innovated to keep knowledge current and enlighten students' challenges in public speaking, such as psychological conditions, language competence, and topical knowledge both internal and external. External challenges, such as learning environments and performance conditions, can have an impact on students' confidence and ability to speak. The research uses The diffusion of innovation theory by Rogers to find out the process of the ESQ Public Speaking Model in the Communication Training Development. This study adopts a qualitative descriptive methodology, collecting data from a variety of sources to analyze the creation and diffusion of the ESQ public speaking model, which includes an analysis of interview findings from ESQ Training Institute students and graduates. As a result, the ESQ Public Speaking method has demonstrated diffusion of innovation towards its module by enhancing the audience's visual, auditory, and kinesthetic delivery modalities and awareness, as well as by developing his own capital, which includes his spiritual, mental, and emotional intelligence. raising individuals' sense of self-worth, communicating ideas clearly, and being conscious of creating a mental and spiritual balance to boost confidence by enabling participants to activate their minds and souls through the law of mindfulness, the ESQ public speaking method creates an internal component in addition to an exterior one, which is its most unique innovation.